Предмет: Математика,
автор: MoreMetal
Помогите доказать, что:
а) tg²α - sin²α = tg²α sin²α
б) sin³α (1 + ctg α) + cos³α (1 + tg α) = sin α + cos α
Ответы
Автор ответа:
0
б) раскрываем скобки у умножаем: (sin^3a+cosa*sin^2a) + (cos^3a+sina*cos^2a)= sina+cosa
выносим общий множитель:
sina+cosa(sin^2a + sin^2a)*(cos^2a+cos^2a)=sina+cosa
sina+cosa=sina+cosa
выносим общий множитель:
sina+cosa(sin^2a + sin^2a)*(cos^2a+cos^2a)=sina+cosa
sina+cosa=sina+cosa
Похожие вопросы
Предмет: Литература,
автор: marinagugi11
Предмет: Алгебра,
автор: smaginaliza82
Предмет: Химия,
автор: swiftkey79
Предмет: Геометрия,
автор: dashatretyakov
Предмет: Физика,
автор: berezniymichai